My Kindergarten - Wells, Rosemary (New York Hyperion Books for Children, 2004)
Emily and her classmates are back, and children follow them through vignettes and enchanting illustrations. Each oversized spread offers a learning experience whether readers are singing songs with Emily and Diane Duck, making valentine cakes with Emily and her mother, or learning about the voting process. Miss Cribbage inspires her students to learn about the world around them in innovative ways.
K - 2
Keywords: Kindergarten - Fiction; Animals - Fiction